Change in drop-landing mechanics over 2 years in young athletes after anterior cruciate ligament reconstruction - Ithurburn, M. P.; Paterno, M. V.; Thomas, S.; Pennell, M. L.; Evans, K. D.; Magnussen, R. A.; Schmitt, L. C. (The American Journal of Sports Medicine, 2019)
Background: While between-limb landing asymmetries after anterior cruciate ligament reconstruction (ACLR) are linked with poor function and risk of additional injury, it is not currently understood how landing symmetry changes over time after ACLR. Purpose/Hypothesis: The purpose was to investigate how double-legged drop vertical jump (DVJ) landing and single-legged drop-landing symmetry changed from the time of return-to-sport (RTS) clearance to 2 years later in a prospective cohort of young athletes after ACLR. It was hypothesized that double-legged DVJ landing and single-legged drop-landing symmetry would improve from the time of RTS to 2 years later. Study Design: Descriptive laboratory study. Methods: The authors followed 64 young athletes with primary, unilateral ACLR for 2 years after RTS clearance. At the time of RTS and 2 years later, between-limb symmetry values for biomechanical variables of interest (VOIs) were calculated with 3-dimensional motion analysis during double-legged DVJ and single-legged drop-landing tasks. VOIs included knee flexion excursion, peak internal knee extension moment, peak vertical ground-reaction force, and peak trunk flexion (for single-legged task only). Symmetry values and proportions of participants meeting 90% symmetry cutoffs were compared between time points. Results: For double-legged DVJ landing, symmetry values for all VOIs and the proportions meeting 90% cutoffs for peak internal knee extension moment and peak vertical ground-reaction force were higher at 2 years after RTS as compared with RTS. For single-legged drop-landing, symmetry values were higher for knee flexion excursion and lower for peak trunk flexion at 2 years after RTS as compared with RTS, but the proportions meeting 90% cutoffs for all VOIs did not differ between time points. Conclusion: